A response to "Likelihood ratio as weight of evidence: A closer look" by Lund and Iyer. (July 2018) - Gittelson, Simone; Berger, Charles E.H.; Jackson, Graham; Evett, Ian W.; Champod, Christophe; Robertson, Bernard; Curran, James M.; Taylor, Duncan; Weir, Bruce S.; Coble, Michael D.; Buckleton, John S.
Highlights: All agree that LR s shall not be imposed on others; this is not current practice. Presenting both an LR, and the basis for it, is current best practice. LR s should not only be assigned where adequate empirical information is available. Even when an opinion is purely subjective, it should be in the form of an LR . The LR is the single most informative summary of evidential weight. Abstract: Recently, Lund and Iyer (L&I) raised an argument regarding the use of likelihood ratios in court. In our view, their argument is based on a lack of understanding of the paradigm. L&I argue that the decision maker should not accept the expert's likelihood ratio without further consideration. This is agreed by all parties. In normal practice, there is often considerable and proper exploration in court of the basis for any probabilistic statement. We conclude that L&I argue against a practice that does not exist and which no one advocates. Further we conclude that the most informative summary of evidential weight is the likelihood ratio. We state that this is the summary that should be presented to a court in every scientific assessment of evidential weight with supporting information about how it was constructed and on what it was based.